Persepsi Konsumen Terhadap Pengambilan Keputusan Pembelian Susu Sapi Perah di Kota Malang - Yohanna, Nesya Kasami Rahayu; Rohman, Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Perception is one of the psychological factors that influence consumer purchasing decisions. The study of consumer perceptions is important because it relates to the idea of consumer perceptions about a product, and can help companies to take appropriate communication policy based on the study of consumer perception. Judging from the dimensions of consumer perceptions in making purchasing decisions can be seen from the three kinds of terms,Â in terms of products, price and promotion. For a company the assessment of consumer perceptions very important role in decision making matters, especially in this case is about the decision of purchasing a product or item. To make a purchasing decisions of consumers will go through a certain process, as well as in the event of a decision to choose the product or brand they will carry out the process in advance may be because they do not want to bear the risk when buying these products, so they will be full of consideration. Such is the importance of consumer decision before making the purchase. Keywords: Perception, purchasing decisions